The Participation of the Breeders: Regional Regulation of Dumai City Concerning Livestock and Pets - Afrizal, Dedy; Al-Amaren, Emad Mohammed; Yusuf, Irfan Murtadho (Faculty of Law, Universitas Sebelas Maret, 2021)
This article aims to look at community participation in implementing Dumai City Act Number 10 of 2008 concerning livestock and pets, namely what impacts arise and what sanctions will be received if they do not comply and what are the anticipatory actions of the breeders so that they will not suffer losses in the future. This study is a qualitative research categorized as sociological juridical research. The data analysis was conducted using descriptive analysis. The results showed that the breeders (livestock farmers)’ lack of understanding on the regulations that had been set was one of the obstacles arising in the implementation of the law. It is hoped that the related parties involved in this Regional Regulation understand the legal sanctions and the impacts that arise from any disobedience acts. From various community backgrounds and in terms of educational factors, cultural factors, geographical aspects, and facility factors, it appears that the government's role in creating all aspects involved in jointly implementing this regional regulation is requiredBesides, breeders must implement these regional regulations as a form of anticipatory action; thus, such livestock and pet activities will not harm themselves and their environment.